Profil Keterampilan Berpikir Kreatif Siswa SMA Negeri 3 Pemalang pada Konsep Solar Cell - Laswadi Arif Tayuda; Joko Siswanto (Universitas PGRI Semarang, 2020)
In order to achieve the goal of national education, students are required to have creative thinking skills, especially in abstract subjects such as chemistry. This study aims to discern the profile of creative thinking in class XI SMA Negeri 3 Pemalang on the Solar Cell concept material for the 2019/2020 Academic Year. The research subjects were 34 students of class XI of Pemalang 3 High School. The research method used is the quantitative descriptive method. The variable of this research is the ability to think creatively measured through written tests in the form of essay questions. Retrieval of data using questions that were developed from four indicators of creative thinking, each question was scored with a score of 1-4 with the criteria of each indicator. Based on the research results of the creative thinking ability of 3 Pemalang State High School students is 16.6 (56%) out of a maximum score of 32. When viewed from the ability of students based on fluency indicators of 1.8 (56%), Flexibility 2.5 (75%), Originality 2.4 (65%), and Elaboration 1.6 (40%). The results of the students' creative thinking abilities are lacking. Therefore, the ability of students to think creatively needs to be improved in the learning process.